2012
DOI: 10.3928/01477447-20120525-35
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hematologic Laboratory Studies in the Postoperative Management of Patients Undergoing Anterior Cervical Diskectomy and Fusion

Abstract: Anterior cervical diskectomy and fusion is a common spinal procedure. Over time, complications and hospital stay have decreased. However, to the authors' knowledge, no study has examined the necessity of routine postoperative hematologic laboratory studies for patients undergoing this procedure.From January 2005 through July 2010, four hundred thirty-four consecutive patients with cervical radioculopathy or myelopathy underwent anterior cervical diskectomy and fusion at 1 institution. Patients who had a concom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…31 Along with that anemia was associated with an increased length of hospital stay, an important marker of hospital costs and predictor of adverse outcomes in high-risk spinal surgery. 32,33 Given that in most cases minimal blood loss and transfusions are required for ACDF surgery, 34,35 the association between anemia with complications in this study suggests that anemia may be a proxy variable that indicates patients’ general poor health, rather than having a direct bearing on surgery itself. Anemia is multifactorial and more so related to patient comorbidities, which include some confounders that could not be accounted for in the present multivariable analysis.…”
Section: Discussionmentioning
confidence: 86%
“…31 Along with that anemia was associated with an increased length of hospital stay, an important marker of hospital costs and predictor of adverse outcomes in high-risk spinal surgery. 32,33 Given that in most cases minimal blood loss and transfusions are required for ACDF surgery, 34,35 the association between anemia with complications in this study suggests that anemia may be a proxy variable that indicates patients’ general poor health, rather than having a direct bearing on surgery itself. Anemia is multifactorial and more so related to patient comorbidities, which include some confounders that could not be accounted for in the present multivariable analysis.…”
Section: Discussionmentioning
confidence: 86%
“…Relatively few studies have examined the utility of postoperative laboratory results, but recent investigations concluded that such testing is not necessary in all patients and should be guided by the patient's medical history, citing potential cost savings. 12,13 In a separate study of postoperative AKI after total joint arthroplasty in 9171 patients, 19% of patients did not have a serum creatinine measurement, suggesting that this is not an isolated issue. 14 Given the adverse outcomes associated with AKI in this study and others, the suggestion by Bell et al that any patient who receives gentamicin prophylaxis should have a serum creatinine determination both preoperatively and postoperatively is sound.…”
mentioning
confidence: 99%